Snacking behavior in adolescents and adults in the United States - Sanchez Alan, Karolina (Kansas State University, 2019)
Understanding snacking behavior in adults and adolescents is important for developing effective marketing campaigns and health interventions. This research provides information about the main motivations to consume different snacks in two age groups. An online survey was conducted with 1551 adults. The reported snacks were classified into 11 groups: sweets, salty snacks, baked products, refined grains, beverages, sandwich or wraps, meats, bars/nuts or seeds, fruits, dairy products, and vegetables. Based on the main motivations to be consumed, these snacks were organized in 3 clusters. Cluster 1: “fun for you" snacks included sweets, salty snacks, and baked products. The main motivations associated with this group were price, social image, social norms, sociability, and affect regulation. Cluster 2: “good for you" snacks included vegetables, dairy products, fruits, and bars/nuts & seeds. The main motivations associated with this group were natural concerns, weight control, and health. Cluster 3: included refined grains, beverages, meats, and sandwich or wraps. The main motivations associated with this group were choice and visual appeal. Motivations to consume different snack groups can vary depending on factors such as gender, race/ethnicity, sociodemographic background, and the place where people live. This research also provides information about the motivations to consume different snack groups based on gender, ethnicity, U.S. region, and annual household income. Results showed that liking and choice were the strongest motivations to consume snacks in all four groups. Convenience, natural concerns, need & hunger, health, weight control, habits, pleasure, and traditional eating were the main motivations to consume “good for you” snacks such as dairy products, fruits, bars, nuts & seeds and were mentioned differently depending on each group. Pleasure, affect regulation, sociability, social image, habits, traditional eating, need & hunger, and visual appeal were related to “fun for you snacks¨ such as salty snacks, baked products, and sweets and were also mentioned differently depending on each group. Snacking behavior in adolescents is a complex process that can be influenced by many different factors. To understand this behavior a study was conducted using an online survey with 1050 adolescents from 13 to 17 years old. This survey included questions related to the snacking behavior of this population using a slightly modified version of the Eating Motivation Survey (TEMS) and the Kids-Palatable Eating Motives Scale. These snack groups were grouped into clusters (three clusters in total) based on their similarity with the 16 motivations from TEMS and the Kids-Palatable Eating Motives. Cluster 1 was considered the group of “fun for you” snacks. These snacks were associated with the following motivations: liking, pleasure, affect regulation, sociability, and social image. Cluster 2 was considered the group of “good for you” snacks and was associated with motivations liking, weight control, natural concerns, health, and traditional eating. Cluster 3 was considered the group of “mixture snacks” and was associated with the motivations of liking, need & hunger, and visual appeal. Knowing the motivations to consume certain types of snacks is important because it can help in developing the right strategies for adults and adolescents based on the reasons that are important for each group.
Keywords: Snacking behavior; Motivation; Food choices